A Biomechanical Study of Laparoscopic 4S‐Modified Roeder and Weston Knot Strength in 3–0 Polyglactin 910 and 3–0 Polydioxanone. Issue 2 (5th December 2012) - Fugazzi, Russell W.; Fransson, Boel A.; Curran, Katie M.; Davis, Howard M.; Gay, John M.
Abstract : Objective: To (1) evaluate biomechanical strength of 4 different laparoscopic knots using 2 suture types, and (2) evaluate carotid artery ligature bursting pressure of 2 knots using a single suture type. Study Design: Biomechanical materials testing. Sample Population: Suture material (3–0 polydioxanone, 3–0 polyglactin 910). Methods: Four knot types were tested: 4S‐modified Roeder (4SMR) Weston plus 3 square throws (W3S); Weston plus 3 granny throws (W3G); and a 4 square throw knot as a control (control); 24 specimens of each knot type were tied with 3–0 polyglactin 910 and 24 of 3 knot types (4SMR, W3S, control) were tied with 3–0 polydioxanone. Suture loop constructs were tested to 3 mm displacement failure and ultimate failure. Carotid artery ligation bursting pressure was tested using 10 samples each of 4SMR and W3S knots with 3–0 polyglactin 910. Results: The W3S, W3G, and controls were similar. The 4SMR was similar to W3S using 3–0 PDS but the 4SMR had lower load to failure and greater elongation than the Weston using 3–0 polyglactin 910. The 4SMR had a higher slippage rate with 3–0 polyglactin 910. All ligatures withstood supraphysiologic pressures. Conclusions: Surgeons using 3–0 polyglactin 910 should consider using the Weston knot with added throws during laparoscopic procedures.